Pérdida de peso en bovinos Bos indicus y Bos taurusdurante el proceso de subasta - Rodríguez Rodríguez, Pablo (2012)
The objective of this work was to determine the effect of commercialization process of a livestock auction on relative and absolute weight loss, according to gender, breed standard, commercial category, animal initial weight and waiting period until sale. During the auctioning process at Asociación Cámara de Ganaderos Unidos del SUR (ACGUS) livestock auction, located in Perez Zeledón, San José, Costa Rica, six hundred twenty nine animals were analyzed. No significant effects of gender and breed standard were found on relative and actual weight loss. However, depending on commercial category, waiting period and animal initial weight (p<0.05) animals may lose between 4.31 and 9.91, 6.16 and 7.31, and 3.52 and 9.54 kilograms per animal, respectively. Breed standard, commercial category and waiting period variables have a significant effect on relative weight loss, not gender and animal initial weigh effects were found. In general, relative weight loss ranged from 1.57 to 2.54%